PENERAPAN DIALOG UNTUK MEMBANGUN KONTEKS PEMBELAJARAN BERBASIS PARADIGMA PEDAGOGI IGNASIAN - Danang Bramasti (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2025)
Context is the beginning of the learning process based on the Ignatian Pedagogy Paradigm (IPP) which must be built before starting learning. Context needs to be built through a dialogue process. The problem is that the dialogue process does not appear in the IPP book published by the Association of Indonesian Jesuit Schools (ASJI), meaning that dialogue is not applied in the learning process. Without dialogue, the learning process will not touch on real problems in the school environment. This paper uses a literature study method that analyzes the book published by ASJI to place the dialogue process in building context. The dialogue process plays a role in building a context that is the basis for making learning materials so that the learning process can change the old context into a new context that is more humane in accordance with the objectives of IPP-based learning. This study uses the content analysis method of 3 series of Jesuit School books, namely: Ignatian Pedagogical Paradigm Curriculum, Education Quality Standards, and Teacher Professionalism Development Design, which are summarized by the Indonesian Jesuit School Association (ASJI).